Fiscal multipliers in recessions - Matthew Canzoneri; Fabrice Collard; Harris Dellas; Behzad Diba (University of Bern, Department of Economics, 2012)
The Great Recession, and the fiscal response to it, has revived interest in the size of fiscal multipliers. Standard business cycle models have difficulties generating multipliers greater than one. And they also fail to produce any significant asymmetry in the size of the multipliers over the business cycle. In this paper we employ a variant of the Curdia-Woodford model of costly financial intermediation to show that fiscal multipliers are strongly countercyclical. In particular, they can take values exceeding two during recessions, declining to values below one during expansions.
Keywords: E32; E62; H3; 330; Government Spending Multipliers; Cyclicality; Financial Frictions; Konjunktur; Antizyklische Finanzpolitik; Multiplikator; Geldpolitische Transmission; Neukeynesianische Makroökonomik; Konjunkturtheorie